PELAKSANAAN AKAD QARD DALAM SYSTEM PENDANAAN ONLINE BERBASIS SYARIAH - Epy Pujiaty; Ahmad Hasan Ridwan (Prodi Ekonomi Syariah Universitas Majalengka, 2023)
This study aims to determine the implementation of qard contracts in a sharia-based online funding system, the study is motivated by the emergence of several fintech companies that offer online funding systems with sharia principles so that they become an alternative choice for Muslim communities who need online loans but labeled Shari`ah. However, in practice there are still sharia fintech that are not in accordance with the implementation that should be shari'ah. Even in 2021 there were 7 cancellations of proof of registration of sharia Fintech Lending by the OJK. This study uses a qualitative method with a literature review approach. Data were obtained from various data sources such as the Koran, journals, books, official news and other references related to the themes discussed in this study. The implementation of qard contracts in a sharia-based online funding system is not prohibited in Islam as long as it does not conflict with syara' law. Qard practice is a form of tabbaru contract practice